Re-enter the syn-(Me,I)Bimane: A Gateway to Bimane Derivatives with Extended π-Systems - Szumski, Oleg; Karmakar, Joy; Grynszpan, Flavio (Synlett, 2021)
syn-α-Diiodobimane (syn-(R2,I)B) is a key intermediate for the derivatization of the bimane core in the α-positions. Here we describe an expeditious method to prepare symmetric α-bimane derivatives, such as syn-(R2,I)B, as well as unsymmetric ones. Our strategy turns the synthesis of α derivatives with extended π-systems practical and affordable. We applied this approach to the synthesis of ethynylbenzaldehyde bearing bimanes as potential selective probes for aldolase class I enzymes.
Keywords: bimane; fluorescence; intermediate; iodobimane; derivatives